2020
DOI: 10.1377/hlthaff.2019.00100
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Decision Aids On Adults Considering Hip Or Knee Surgery

Abstract: Trials of decision aids developed for use in shared decision making find that patients engaged in that process tend to choose more conservative treatment for preference-sensitive conditions. Shared decision making is a collaborative process in which clinicians and patients discuss tradeoffs and benefits of specific treatment options in light of patient values and preferences. Decision aids are paper, video, or web-based tools intended to help patients match personal preferences with available treatment options… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…Three studies indicate mixed association between race and decision‐making. In two, minority (non‐white) patients were significantly less likely to choose surgery (Hurley et al., 2020; Kwoh et al., 2015), another found race was not significantly associated in shoulder and elbow conditions (Modi et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies indicate mixed association between race and decision‐making. In two, minority (non‐white) patients were significantly less likely to choose surgery (Hurley et al., 2020; Kwoh et al., 2015), another found race was not significantly associated in shoulder and elbow conditions (Modi et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…78 Modi, et al, 2014 Chung et al, 2006;Glassman et al, 2007;Hawker et al, 2004;Nelson et al, 2020;Pizones et al, 2017;Somerson et al, 2018;Trask et al, 2020;Wouters et al, 2019;Yoo et al, 2018;Zeni et al, 2010) (Behairy et al, 2003;G. A. Hawker et al, 2001;Modi et al, 2014) Pain: More (surgical), less (nonsurgical) 6 0 1 (Chung et al, 2006;Glassman et al, 2007;Kwoh et al, 2015;Riffin et al, Perceptions Expectations: Higher (surgical) 5 0 0 (Frankel et al, 2012;Kwoh et al, 2015;Matthies et al, 2020;Modi et al, 2014;Wouters et al, 2019) Psychological/body image/ distress: Higher (surgical) 5 0 0 (Chung et al, 2006;Glassman et al, 2007;Hurley et al, 2020;Pizones et al, 2017;Wouters et al, 2019) Note: Significant finding: studies that reported significant finding in line with the Factor Description. Significant opposing finding: studies that reported significant result favouring the opposing option to the Factor Description.…”
Section: Qualitymentioning
confidence: 99%
“…Reasons for this lower willingness to undergo TKR include less familiarity with the procedure, or erroneous beliefs about outcomes, duration of hospitalization and recovery 33e35 . The remaining studies included a majority of white participants, with null results in two randomized trials 13,15 , a lower rate of surgery in the PtDA group in one trial 14 and two observational studies 36,37 , and the opposite result in another observational study 38 . Therefore, the current evidence is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…2 Further, a recent analysis of 5751 patients with hip and knee osteoarthritis found that patients exposed to a patient decision aid were more likely to have joint replacement surgery (hip: OR=2.6; knee: OR=1.8) compared with patients who had not been exposed. 24 Another reason why patient decision aids may not help patients avoid unnecessary care is that they might not technically be 'patient decision aids. ' Many resources are labelled as 'patient decision aids' when, in fact, they do not include the necessary information to certify as a decision aid or support shared decision making.…”
Section: Biased Presentation Of Low-certainty Evidence Is Misleading ...mentioning
confidence: 99%